Exploring the Relationship between Science Content Knowledge and Science Teaching Self-Efficacy among Elementary Teachers - Amy Catalano; Lauren Asselta; Alana Durkin (IAFOR Journal of Education, 2019)
Elementary school teachers are commonly known to have low self-efficacy in mathematics and science. Previously conducted research on science teaching self-efficacy and content knowledge has often focused on whether methods courses, professional development or other interventions improve both self-efficacy and content knowledge among elementary teachers. This study investigated whether teachers’ knowledge of science content influenced their levels of self-efficacy, and compared teachers’ who were in a STEM education graduate degree program to teachers and students in a regular elementary teaching program. The participants of this study were 82 in-service and 27 pre-service elementary teachers in affiliation with a large northeastern university. The participants completed a science self-efficacy survey (STEBI-B) and a science content knowledge survey called the Science Beliefs Tests. The results of this study found that pre-service teachers had a higher self-efficacy score in comparison to in-service teachers. Most participants were able to answer a little more than half of the Science Beliefs questions correctly. Additionally, there was a negative relationship between one’s belief that they could teach science effectively and their Science Beliefs score, meaning that the more science self-efficacy they possessed, the lower their science knowledge. It is important that teachers become aware of their lack of content knowledge in order to remedy the insufficiency, and to avoid passing along misconceptions to their students. If teachers believe that they have high self-efficacy, they may not be aware that they must continually improve their science content knowledge. Accordingly, teachers can benefit from continued education in topic areas where they scored the lowest.